Magnitude of Malarial Parasite Among the Blood Donors From Endemic and Non-Endemic Area of Bangladesh: A Cross Sectional Study (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Transfusion transmitted malaria is one of the feared dangers in transfusion services. Parasite density is often quite low in healthy donors to detect the magnitude of plasmodium among the blood donors. To develop awareness about transfusion transmitted malaria and to find out the socio-demographic characteristics of blood donors from endemic and non-endemic areas.Materials and methods: This cross-sectional study was conducted in three Transfusion Medicine Departments of Chattogram, Cox's Bazar and Dhaka District from February 2015 to July 2015. Here, 150 consecutive healthy blood donors were included in two groups equally (Group I endemic and Group II non-endemic). Malaria screening was done by rapid diagnostic method.  Results: Most of the participants were in 21-30 years age group, 44(58.7%) and 45(60.0%) in group I and group II respectively. Male to female ratio was 11.5:1 (Male 69 and female 6). Again, 50(66.7%) in group I and 67(89.3%) in group II came from urban area. Previous history of fever (Within 3 months) was found 18(24.0%) in group I and 6(8.0%) in group II. Malarial parasite was detected 1(1.3%) in group I but none in group II (p>0.05, nonsignificant). Conclusion: This work will be helpful in improving preventive strategies for secure blood transfusions.JCMCTA 2024 ; 35 (1) : 89-94